Histological Spectrum of Idiopathic Noncirrhotic Portal Hypertension in Liver Biopsies From Dialysis Patients. (September 2015) - Lee, Hwajeong; Ainechi, Sanaz; Singh, Mandeep; Ells, Peter F.; Sheehan, Christine E.; Lin, Jingmei
Objectives . Liver biopsy is performed for various indications in dialysis patients. Being a less-common subset, the hepatic pathology in renal dialysis is not well documented. Idiopathic noncirrhotic portal hypertension (INCPH) is a clinical entity associated with unexplained portal hypertension and/or a spectrum of histopathological vascular changes in the liver. After encountering INCPH and vascular changes of INCPH in 2 renal dialysis patients, we sought to further investigate this noteworthy association. Materials and methods . A random search for patients on hemodialysis or peritoneal dialysis with liver biopsy was performed. Hematoxylin and eosin, reticulin, trichrome, and CK7 stains were performed on formalin-fixed, paraffin-embedded tissue sections. Histopathological features were reviewed, and the results were correlated with clinical findings. Results . In all, 13 liver biopsies were retrieved. The mean cumulative duration of dialysis was 50 months (range = 17 months to 11 years). All patients had multiple comorbidities. Indications for biopsy were a combination of abnormal liver function tests (6), portal hypertension (4), ascites (3), and possible cirrhosis (3). Two patients with portal hypertension underwent multiple liver biopsies for diagnostic purposes. All (100%) biopsies showed some histological features of INCPH, including narrowed portal venous lumen (9), increased portal vascular channels (8), shunt vessels (3), dilated sinusoids (9), regenerative nodule (5), and features of venous outflow obstruction (3). No cirrhosis was identified. Conclusion . Liver biopsies from patients on dialysis demonstrate histopathological vascular changes of INCPH. Some (31%) patients present with portal hypertension without cirrhosis. The histological changes may be reflective of underlying risk factors for INCPH in this group.